2012
DOI: 10.5001/omj.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Fine Needle Aspiration Cytology versus Fine Needle Capillary Cytology in Thyroid Nodules

Abstract: The results indicated that there was no significant difference between the two techniques; if done in tandem can give better and accurate cytological diagnosis. In highly cellular lesions, in which abundant material was obtained, FNC was more likely to be diagnostically superior, but FNA can diagnose most of the lesions. In less cellular lesions, FNA is more likely to be diagnostically superior to FNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 13 publications
3
33
0
1
Order By: Relevance
“…Similar observations were also made by Ramachandra et al 9 Out of 91 samples, 7 of them were of neoplasm in nature and 81 were of non-neoplastic lesions. Similar observations were also made by Tauro et al 8 Out of 50 cases 49 were of non-neoplasm and 1 case reported of malignancy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar observations were also made by Ramachandra et al 9 Out of 91 samples, 7 of them were of neoplasm in nature and 81 were of non-neoplastic lesions. Similar observations were also made by Tauro et al 8 Out of 50 cases 49 were of non-neoplasm and 1 case reported of malignancy.…”
Section: Discussionsupporting
confidence: 86%
“…Study by Tauro et al on 50 patients presented that the most affected age group as 40-49 years (36%). 8 Female preponderance (86.81%) was observed in the study. Similar observations were also made by Ramachandra et al 9 Out of 91 samples, 7 of them were of neoplasm in nature and 81 were of non-neoplastic lesions.…”
Section: Discussionmentioning
confidence: 47%
“…Tauro et al [15] found that dignostically FNAC was notably better, producing more superior specimen compared to FNNAC. Also, FNNAC exhibited more diagnostically adequate specimen.…”
Section: Discussionmentioning
confidence: 99%
“…It was drained using aspiration technique. The cyst disappeared after colloid was drained and hence FNA becomes therapeutic procedure [15] . Thus, we observed that both techniques had comparable scores in cases of colloid cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid swellings/nodules demand a sequence of investigations to rule out the possibility of a neoplasm or thyroiditis (11).FNAC is an important tool for the cytological assessment of patients with superficial as well as deep seated lesions. But this technique is frequently complicated by aspiration of significant quantities of blood particularly in vascular organs or haemorrhagic tumours which compromise cellular preservation and interpretation.…”
Section: Discussionmentioning
confidence: 99%